Anna Archer: capstone - Archer, Anna, artist (Colorado State University. Libraries, 2019)
The artist's statement: During my time at CSU my graphic design work as consisted of working with a variety of color while maintaining an application of type that fits with each project. I typically create projects that are simplistic or minimal but the message still gets across to the viewer but maximizing surface area. With a few projects, I have ventured away from the minimal approach, I have experimented with busy patterns and pairing them with vibrant colors.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design